Metallurgical and Mechanical characterization of A319 Aluminum Alloy Casting Solidified Under Mold Oscillation - Kumar S.; Tewari S.P. (My University, 2025)
This paper deals with the effect of mold oscillation (during alloy solidification) on the metallurgical and mechanical properties of A319 alloy casting. For the evaluation of aforesaid effect, oscillatory amplitudes of 5, 10, 15, and 20 µm with a constant frequency of 100 Hz were used. Results obtained under oscillatory conditions were compared with those of castings prepared under stationary condition. Metallurgical properties were examined through microstructure, tensile fracture SEM and SEM image of test specimens prepared under different conditions of solidification. Grain refinement was obtained through mold vibration. SEM image of the tensile fractured surface in all the cases reveals a mixed mode of fracture consisting of fine dimples and intergranular decohesion fracture surfaces. Small dimples indicate that some plastic deformation has taken place before fracture. Cleavage formation may be attributed to the presence of hard and brittle Al2Cu and FeSi phases. Likewise, mechanical properties of oscillatory casting were examined through the tensile and microhardness test and compared with similar properties obtained under stationary condition. © 2017, American Foundry Society.